(b – 3c)(8b + 5c) =
(5b – 4c)(3b – 2c) =
(3x-2y) (x+y)=
(5-4b) (2a- b)=
(6+3b) (7+b)=
(m-4)(5+3m)=
(-4x- 2y)(4y+6x)=
(y-4z)(2z- 3y)=
(a+3)(2a-5)=
(-4a-b)(3b- 2a)
proszę szybko daje 100pkt



Odpowiedź :

a) 8b²+5bc-23bc-15c²=8b²-15c²-18bc

b)15b²-10bc-12bc+8c²=15b²+8c²-22bc

c)3x²+3xy-2xy-2y²=3x²-2y²+xy

d) 10a-5b-8ab+4b²

e)42+6b+21b+3b²=3b²+27b+42

f) 5m+3m²-12m-20=3m²-7m-20

g)-16xy-24x²-8y²-12xy=-28xy-8y²-24x²

h)2zy-3y²-8z²+12zy=14zy-3y²-8z²

i)2a²-5a+6a-15=2a²+a-15

k)-12ab+8a²-3b²+2ab=8a²-10ab-3b²

Proszę o naj ;)

Odpowiedź:

1. (b - 3c)(8b + 5c) = 8b^2 + 5bc - 24bc - 15c^2 = 8b^2 - 15c^2 - 19bc

2. (5b - 4c)(3b - 2c) = 15b^2 - 10bc - 12bc + 8c^2 = 15b^2 + 8c^2 - 22bc

3. (3x - 2y)( x + y) = 3x^2 + 3xy - 2xy - 2y^2 = 3x^2 - 2y^2 + xy

4. (5 - 4b)(2a - b) = 10a - 5b - 8ab + 4b^2

5. (6 + 3b)(7 + b) = 42 + 6b + 21b + 3b^2 = 3b^2 + 27b + 42

6. (m - 4)(5 + 3m) = 5m + 3m^2 - 20 - 12m = 3m^2 - 7m - 20

7. (-4x - 2y)(4y + 6x) = -16xy + 24x^2 - 8y^2 - 12xy = 24x^2 - 8y^2 - 28xy

8. (y - 4z)(2z - 3y) = 2yz - 3y^2 - 8z^2 + 12yz = -3y^2 - 8z^2 + 14yz

9. (a + 3)(2a - 5) = 2a^2 - 5a + 6a - 15 = 2a^2 + a - 15

10. (-4a - b)(3b - 2a) = -12ab - 8a^2 - 3b^2 + 2ab = 8a^2 - 3b^2 - 10ab

Liczę na naj ^^